Microplastic and macroplastic ingestion by a deep diving, oceanic cetacean: The True's beaked whale Mesoplodon mirus. (April 2015) - Lusher, Amy L.; Hernandez-Milian, Gema; O'Brien, Joanne; Berrow, Simon; O'Connor, Ian; Officer, Rick
Abstract: When mammals strand, they present a unique opportunity to obtain insights into their ecology. In May 2013, three True's beaked whales (two adult females and a female calf) stranded on the north and west coasts of Ireland and the contents of their stomachs and intestines were analysed for anthropogenic debris. A method for identifying microplastics ingested by larger marine organisms was developed. Microplastics were identified throughout the digestive tract of the single whale that was examined for the presence of microplastics. The two adult females had macroplastic items in their stomachs. Food remains recovered from the adult whales consisted of mesopelagic fish ( Benthosema glaciale, Nansenia spp., Chauliodius sloani ) and cephalopods, although trophic transfer has been discussed, it was not possible to ascertain whether prey were the source of microplastics. This is the first study to directly identify microplastics <5 mm in a cetacean species. Highlights: True's beaked whales stranded in Ireland were examined for anthropogenic debris. One adult female had microplastics throughout her digestive tract. Both adult females ingested macroplastic items. Dietary analysis suggests the whales fed on mesopelagic fish. Abstract : Dietary study finds microplastic and macroplastic ingestion by rare, oceanic, predatory cetaceans stranded in Ireland.